Potential halal food colorants and active pharmaceutical ingredients in 24 Malaysian traditional vegetables (ulam) - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (2014)
Synergistic combination of two National Key Economic Areas (NKEAs) in healthcare and agricultural sectors counts for promoting extensive exploitation of Malaysia’s mega-biodiversity to develop pharmaceuticals and related products from natural resources. Additionally, it is noted that nowadays halal products are gaining wider recognition as a new benchmark for safety measure and quality assurance especially among the Muslim consumers. In this study, we established quantification of a group of plant pigments which are potentially to be introduced as halal active pharmaceutical ingredients (API) and natural food colorants from 24 species of local traditional vegetables (ulam), identified as neoxanthin, violaxanthin, lutein, zeaxanthin, β-cryptoxanthin, α-carotene and β-carotene. These targeted biocolorant and phytopharmaceutical ingredients were found to be comparable in concentrations after being developed through series of phytochemical extraction, purification and finally analysed through HPLC. Results obtained shown that Sauropus androgynus contained highest amount of neoxanthin, violaxanthin and β- cryptoxanthin at 142.40 ± 3.57, 28.06 ± 0.65 and 0.07 ± 0.00 mg/g DW, respectively. Highest accumulation of lutein and α-carotene were observed in Centella asiatica at 16.53 ± 0.97 and 2.14 ± 0.12 mg/g DW accordingly. Piper sarmentosum accumulated high zeaxanthin content (123.45 ± 12.3 mg/g DW) whereas Oenanthe javanica has the largest amount of β-carotene (3.09 ± 0.06 mg/g DW). The extracted yellow-to-red pigments can be further commercialised especially in the halal market for pharmaceutical and coloring products. The significant outcome of this research will be new dicoveries of natural resources for food colorant and API which covers not only the shariah requirement, but also the hygiene, sanitation and safety aspects.